Potential Analysis of Organic Fertilizer Business Development from Beef Cattle Manure - Muhammad Fikri Hijami; Miftakhul Arifin; Endah Puspitojati (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
This study aimed to determine the availability of technical, economic, and social aspects that support the development of organic fertilizer business based on beef cattle manure in Karangtengah Prandon Village, Ngawi District, Ngawi Regency, Indonesia. The research method used interviews, questionnaires, and observation. This study involved 37 respondents who were selected by proportional random sampling technique. The data analysis was carried out by descriptive analysis. The results revealed that the availability of technical aspects has a potential of 64.4 percent, the availability of economic aspects has a potential of 62.7 percent, and the availability of social aspects has a potential of 47.9 percent. The most potential factor of technical aspect was the raw material availability in the location. Meanwhile, social factors, such as labor skills and leader community supports need to be increased. Developing a fertilizer business in Karang Tengah Prandon village may be accomplished by empowering farmers to turn fertilizer into a business.